Matrix-biased excitatory and inhibitory inputs to the striatum involving external segment of the globus pallidus - Karube, Fuyuki; Kobayashi, Kenta; Fujiyama, Fumino (Frontiers in Cellular Neuroscience, 2025)
IntroductionThe external segment of the globus pallidus (GPe) is traditionally viewed as a relay nucleus within the indirect basal ganglia pathway. However, a subpopulation of GPe neurons projects directly to the striatum, raising questions about their compartmental and cell-type-specific targeting.MethodsTo address this issue, we employed neural tracing and ex vivo whole-cell patch-clamp recordings with optogenetics using adeno-associated viral vectors in rats. Anatomical observations and intersectional labeling techniques were applied to examine spatial relationships of projections among the striatum, GPe, and ventral thalamus.ResultsGPe axons exhibited a strong bias toward the matrix compartment of the striatum. This biased projection originated from both subthalamic nucleus-targeting and striatum-targeting GPe neurons. In contrast, striatal projections to the GPe arose from both matrix and striosome compartments. Optogenetic stimulation of GPe axons elicited inhibitory postsynaptic currents in medium spiny neurons (MSNs) and cholinergic interneurons (CINs) in the matrix compartment. Cesium-based recordings indicated distal synaptic contacts in MSNs. Anatomical data also revealed proximal appositions of GPe axons to CIN somata and dendrites. Excitatory inputs from motor cortical areas and ventral thalamic nuclei also preferentially targeted the matrix. Furthermore, optogenetic stimulation of ventral thalamic axons elicited excitatory postsynaptic currents in GPe neurons. Intersectional labeling revealed substantial overlap between striatal neurons and axons of GPe neurons, both of which were innervated by the same population of ventral thalamic neurons.DiscussionThese findings suggest that convergent cortical and thalamic excitation of both the striatum and GPe may induce feedforward inhibition within the striatal matrix, particularly onto CINs. This mechanism may contribute to the fine-tuning of striatal output in motor-related basal ganglia circuits.